The Role of Law in Protecting Employees Against Discrimination in the Workplace - Whendy Brasilianna; Wieke Dewi Suryandari; Mohamad Tohari (Lembaga Pengembangan Kinerja Dosen, 2026)
Discrimination in the workplace is a problem that can hinder the creation of a fair and inclusive work environment. Discrimination can take the form of differential treatment of employees based on gender, race, religion, disability, sexual orientation, or other factors unrelated to individual performance and competence. To address this issue, the law plays a crucial role in providing employee protection to ensure equality and non-discrimination in the workplace. Various legal instruments, both national and international, regulate employee protection from discrimination, including the Employment Law, the Human Rights Law, and conventions issued by the International Labour Organization (ILO). However, the effective implementation of these regulations remains a challenge, particularly in terms of implementation, enforcement, and employee awareness of their rights. This study aims to analyze the role of law in protecting employees from discrimination in the workplace by examining applicable regulations and the challenges in their implementation. The research method used is a normative juridical method, which focuses on the study of relevant laws and legal principles. The analysis is conducted on national legal provisions and international legal instruments as references for protecting workers from discrimination. Furthermore, this study identifies barriers to legal implementation and offers recommendations to improve the effectiveness of legal protection for employees. This analysis is expected to provide insight into the urgency of regulatory reform and strengthening so that the law can play an optimal role in creating a fairer and more discrimination-free work environment.